Effects of drug abuse and mental disorders on oral health: a case report - Ortiz Magdaleno, Marine; Romo Ramirez, Gabriel (Journal of the Pakistan Medical Association, 2022)
Substance use disorders, related to mental health issues can lead to oral pathologies. The purpose of this case report was to identify the oral conditions and manifestations in a 28-year-old male narco-dependent schizophrenic who smoked tobacco and marijuana. In intra-oral clinical exploration, poor oral hygiene, excessive tartar formation and dental plaque were observed, and the diagnosis of severe chronic periodontitis was established. The choice of a treatment plan in such patients is complex because the consequences of an invasive treatment can aggravate the psychological state and emotional stability leading to a negative effect on behaviour and mental health due to edentulism. The effects of excessive drug consumption related to schizophrenia can cause poor oral hygiene habits leading to oral pathologies and the loss of teeth. Keywords: drugs, schizophrenia, oral manifestations, mental health, oral pathologies.